(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article is devoted to the introduction and development of halal business practices in Uzbekistan. It analyzed international experience in the field of halal finance, investments and insurance, and considered promising directions for Uzbekistan. In particular, such issues as the development of halal financial institutions, the formation of the halal consumer goods and services market, the support of halal entrepreneurship, and the formation of halal business culture were covered.